The Paradigm of Justice in The Black Heralds: «a single heartbeat; a single rhythm» - Velazco Lévano, Nilton César (2019)
In this article we present some keys that allow to demonstrate the formulation of the paradigm of justice and its utopian sense of the humanity that develops César Vallejo in The Black Heralds. This paradigm is constructed from its aesthetics curdled from the Andean, family, social, cultural, anthropological, historical, political and juridical experience. This poetic work is a foundation for the whole corpus Vallejiano and marks the course of what would be its peculiar humanism and its cravings for human justice, which constitutes itself in the thread of all its work. Therefore, his message is effective and urgent to be announced and revalued.